Ligament Augmentation and Reconstruction System Failures in Repair of Grade V Acromioclavicular Joint Dislocation - Martin K.-H. Li; David Woods (Case Reports in Orthopedics)
The Ligament Augmentation and Reconstruction System® (LARS®) represents a popular synthetic anatomical reduction method for acromioclavicular joint dislocation by means of coracoclavicular ligament reconstruction. To our knowledge, no early failure has been documented in the literature. We present two unusual cases of LARS failure, one at four months after implant and the other at three weeks, without obvious causes, requiring re-do reconstruction, and discuss potential contributory factors.